2010
DOI: 10.1111/j.1365-294x.2010.04774.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic discontinuities and disequilibria in recently established populations of the plant pathogenic fungus Mycosphaerella fijiensis

Abstract: Dispersal processes of fungal plant pathogens can be inferred from analysis of spatial genetic structures resulting from recent range expansion. The relative importance of long-distance dispersal (LDD) events vs. gradual dispersal in shaping population structures depends on the geographical scale considered. The fungus Mycosphaerella fijiensis, pathogenic on banana, is an example of a recent worldwide epidemic. Founder effects in this species were detected at both global and continental scale, suggesting stoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 89 publications
4
57
1
4
Order By: Relevance
“…Indeed, frequent long-distance (up to several kilometers) ascospore movement by wind dispersal has been suspected previously in this species (Burt et al, 1998;Amil et al, 2007). Thus, in contrast with our previously published work (Halkett et al, 2010;Rieux et al, 2011), we did not detect any genetic discontinuities over the area studied. However, this area exhibits some topographical differences in comparison to the areas previously considered.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Indeed, frequent long-distance (up to several kilometers) ascospore movement by wind dispersal has been suspected previously in this species (Burt et al, 1998;Amil et al, 2007). Thus, in contrast with our previously published work (Halkett et al, 2010;Rieux et al, 2011), we did not detect any genetic discontinuities over the area studied. However, this area exhibits some topographical differences in comparison to the areas previously considered.…”
Section: Discussioncontrasting
confidence: 55%
“…The first detected a pattern of isolation by distance (IBD) along a 300-km-long transect, suggesting a continuous range expansion of the disease at the regional scale through the natural and gradual dispersal of spores (Halkett et al, 2010). However, a break in allelic frequencies was detected in the middle of this transect.…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of two M. fijiensis populations with a recent colonization history (Costa Rica and Cameroon), Halkett et al (2010) detected low-to-moderate genetic differentiation, but they suggested continual expansion of this phytopathogen as a result of gradual dispersion of spores over several hundred kilometers. The most recent analysis of the worldwide population structure of M. fijiensis showed that the global expansion of this wind-dispersed pathogen occurred via its unique successful introduction into the African continent and several introductions into the American continent (Robert et al, 2012), although samples from the Brazilian M. fijiensis population were not included in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in populations of M. fijiensis showed that this fungus exhibits high genetic variability (Rivas et al, 2004;Halkett et al, 2010). Recently, Robert et al (2012) showed that Southeast Asia was the center of origin of M. fijiensis by analyzing the introduction routes of M. fijiensis in four continents using isolates from 37 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Various molecular marker systems have been used to study the genetic variability of populations of M. fijiensis, including random amplified polymorphic DNA (RAPD) (Johanson et al, 1994), restriction fragment length polymorphism (RFLP) (Carlier et al, 1996;Hayden et al, 2003), single nucleotide polymorphism (SNP) (Zandjanakou-Tachin et al, 2009), and microsatellite (Halkett et al, 2010;Robert et al, 2012) markers, which have demonstrated high genetic variability in most populations studied.…”
Section: Introductionmentioning
confidence: 99%